Unique compound with anti-allergic action: inhibition of Lyn kinase activity by KIRA6 - Matsushima, Goshi; Matsui, Yuri; Okamoto, Hanano; Umeda, Nagisa; Kakimoto, Mai; Mino, Megumi; Nakagawa, Tadashi; Ishii, Kaori; Matsuo, Yoshimi; Matsubara, Daiki; Tanaka, Akio; Ogata, Koji; et al. (Frontiers in Pharmacology, 2025)
Mast cells and basophils play important roles in allergic disorders associated with specific antigens and IgE. Crosslinking of the high-affinity IgE receptor (FcεRI) by specific antigens activates several tyrosine kinases, such as Lyn and spleen-associated tyrosine kinase (Syk), resulting in the release of calcium ions (Ca2+) from the endoplasmic reticulum (ER) into the cytoplasm. As Ca2+ release from the ER is essential for the release of pro-inflammatory mediators, ER stress-related molecules, such as inositol-requiring enzyme 1α (IRE1α), may play roles in mast cell and basophil activation. However, the associations between ER stress-related molecules and mast cell and basophil activation remain unclear. In this study, we aimed to investigate the roles of ER stress-related molecules in mast cell and basophil activation. Activation of the IRE1α-spliced form of the X-box binding protein 1 (sXBP1) axis, an ER stress-related pathway, was observed during the antigen-induced activation of mast cells. Moreover, the IRE1α inhibitor, KIRA6, suppressed antigen-induced release of pro-inflammatory mediators from rat basophilic leukemia (RBL)-2H3 cells, bone marrow-derived mast cells (BMMCs), human basophils, and human mast cells at low doses (<1 μM). However, to our surprise, IRE1α knockout did not inhibit antigen-induced release of pro-inflammatory mediators. Instead, KIRA6 blocked the antigen-induced activation of Syk by inhibiting kinase activity of Lyn. Additionally, KIRA6 exerted anti-allergic effects in vivo. Overall, our findings suggest that KIRA6 prevents allergic reactions by inhibiting the kinase activity of Lyn via an IRE1α-independent pathway.